2022
DOI: 10.3389/fendo.2022.1006101
|View full text |Cite
|
Sign up to set email alerts
|

Exploring anti-androgen therapies in hormone dependent prostate cancer and new therapeutic routes for castration resistant prostate cancer

Abstract: Androgen deprivation therapies (ADTs) are important treatments which inhibit androgen-induced prostate cancer (PCa) progression by either preventing androgen biosynthesis (e.g. abiraterone) or by antagonizing androgen receptor (AR) function (e.g. bicalutamide, enzalutamide, darolutamide). A major limitation of current ADTs is they often remain effective for limited durations after which patients commonly progress to a lethal and incurable form of PCa, called castration-resistant prostate cancer (CRPC) where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 126 publications
0
10
0
Order By: Relevance
“…Patients in the high-risk group were sensitive to BIBW2992, bicalutamide, doxorubicin, embelin, gemcitabine, midostaurin, parthenolide, pazopanib, rapamycin, salubrinal, sunitinib, and tipifarnib, which can be used to treat a wide range of tumors. Bicalutamide, a second-generation oral nonsteroidal antiandrogen, is widely used to treat prostate cancer and triple-negative breast cancer 43 , 44 . Sunitinib is a tyrosine kinase inhibitor with antiangiogenic properties that plays a crucial role in the treatment of metastatic renal cell carcinoma 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the high-risk group were sensitive to BIBW2992, bicalutamide, doxorubicin, embelin, gemcitabine, midostaurin, parthenolide, pazopanib, rapamycin, salubrinal, sunitinib, and tipifarnib, which can be used to treat a wide range of tumors. Bicalutamide, a second-generation oral nonsteroidal antiandrogen, is widely used to treat prostate cancer and triple-negative breast cancer 43 , 44 . Sunitinib is a tyrosine kinase inhibitor with antiangiogenic properties that plays a crucial role in the treatment of metastatic renal cell carcinoma 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Morgentaler suggested that the solution to this paradox lies in the concept of saturation, “in which maximal stimulation of prostate cancer growth is achieved at some relatively low concentration of testosterone.” 28 Fowler and Whitmore first proposed this model in 1981 29 . Further research aims to elucidate castrate‐resistant prostate cancer, androgen receptor mutations 30 and targeting of androgen signaling 31 …”
Section: Outstanding Answers Todaymentioning
confidence: 99%
“…enzalutamide, apalutamide, and darolutamide) as well as taxane-based chemotherapy (e.g. docetaxel and cabazitaxel) [ 5 , 6 ]. Options following standard treatments are often limited in their effectiveness [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%